Distributional effects of marine protected areas. A study of the North-East Atlantic cod fishery - Sumaila, Ussif Rashid; Armstrong, Claire W. (Universitetet i Tromsø, 2003)
This paper studies the distributional effects of the implementation of a marine protected area (MPA) for the North-East Atlantic cod stock. A bioeconomic cohort model with two agents targeting different age groups is used to examine how the establishment of an MPA may affect the payoffs to the two main vessel types used to exploit cod, namely, trawlers and coastal vessels. Cooperative and non-cooperative behaviour between the management of the two vessel groups are used to describe the existence or non-existence of efficient management in the fishable area. The model includes a shock in the form of a recruitment failure. A key result that emerges from this contribution is that depending on the ex ante status quo and ex post management, we may observe win-win, lose-lose or win-lose situations as a result of an MPA implementation. For instance, when the ex post management is cooperation, both agents in our model gain, while ex post non-cooperative behaviour results in gains only to the coastal fleet with the implementation of MPAs. The study also shows that even without cooperation outside the MPA, both groups would prefer a 50% reserve to the non cooperative outcome in the absence of an MPA. This is an indication that a reserve may well be preferred to a badly managed non-reserve fishery even when management outside the reserve is non-existent.